I carry what I can, i make a yard wherever possible: research and invention based on the narratives of migrant women silenced by official history in the construction of the new federal capital. (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
This study stems from the research and creative process of the performance "I Carry What I Can, Make a Backyard Wherever Possible", by the Coletivo Entrevazios (DF). It is rooted in the sensitive listening of stories from migrant women living in the oldest regions of the Federal District. In contrast to the official narrative about the construction of the new federal capital, this investigation proposes a memory politics that values the everyday life, courage, and resistance of these women, with the Barraca de Memórias action as a trigger for these silenced narratives.
Keywords: Objects; Memory; Women; Migration; Brasília